Pengembangan Handout Materi Bangun Ruang Sisi Datar Kelas VIII Berdasarkan Pendekatan Pembelajaran Matematika Realistik - Lillah Nurfadlilah; Sirojudin Wahid; Muhamad Ali Misri (Jurnal Tadris Matematika, 2022)
Learning resources in the form of textbooks and LKS often make students feel bored during learning activities, because these two learning sources often only contain formulas and material, without any comprehensive explanation of mathematical concepts. Therefore, there is a need for innovation in the learning resources used in schools. This research is aimed at developing handouts for class VIII on flat sided of three-dimensional material based on the Realistic Mathematics Learning approach. This type of research is research and development (Research and Development) with the 4-D model development method by Thiagarajan, namely: 1) Define, 2) Design, 3) Develop, and 4) Disseminate. The results of the material expert's validation of the handout showed an average value of 0.8106 with high validity criteria and was declared feasible. The results of the media expert's validation of the handout showed an average value of 0.8698 with high validity criteria and was declared feasible. From the post-test results of the experimental class, it was found that almost all students passed. The results of the Independent Sample T-Test at the testing stage for the use of the experimental class showed a value of 0.034, thus a significance value of <0.05 was obtained, which means that there was a significant difference in improving student learning outcomes between the experimental class and the control class. This is in line with the students' responses at the usage trial stage obtaining a percentage of 79% with the criteria that almost all students gave a positive response to the handout.